The Analysis of Students’ Cognitive Ability Based on Assesments of the Revised Bloom’s Taxonomy on Statistic Materials - Rahayu, Ayu (European Journal of Multidisciplinary Studies, 2018)
This research is descriptive research with quantitative approach that aims to describe students’ cognitive abilities based on assessment of the Revised Bloom’s Taxonomy on statistics material. The subjects of this research were 36 students of class XI Science. Data obtained by using a research instruments that was learning achievement test accordance with the Revised Bloom’s Taxonomy on statistic material. The data analysis technique was descriptive analysis. The results of this research indicate that: (1) on factual knowledge the ability percentage of student’s cognitive process begins from the highest to the lowest percentage that is the level of ability C1 (remember), C2 (understand), C3 (apply), C4 (analyze), C5 (evaluate), and C6 (create); (2) on conceptual knowledge the ability percentage of students’ cognitive process begins from the highest to the lowest percentage that is the level of ability C1 (remember), C2 (understand), C3 (apply), C4 (analyze), C6 (create), and C5 (evaluate); (3) on procedural knowledge the ability percentage of students’ cognitive process begins from the highest to the lowest percentage that is the level of ability C1 (remember), C2 (understand), C3 (apply), C4 (analyze), C6 (create), and C5 (evaluate); (4) on metacognitive knowledge the ability percentage of students’ cognitive process begins from the highest to the lowest percentage that is the level of ability C1 (remember), C2 (understand), C3 (apply), C4 (analyze), C5 (evaluate), and C6 (create).